Biochemical Response to Hyperbaric Oxygen Treatment of a Transhemispheric Penetrating Cerebral Gunshot Injury - Thelin, Eric Peter; Bellander, Bo-Michael; Nekludov, Michael (Frontiers in Neurology, 2015)
Hyperbaric oxygen (HBO) therapy has been suggested a treatment option in order to reduce the development of secondary insults succeeding traumatic brain injury. This case report studied the course of a 23-year-old gentleman with a close range transhemispheric gunshot wound. The biochemical parameters, using a multi-modal monitoring in the neuro-intensive care unit, improved following HBO treatment.